PENGARUH UKURAN PERUSAHAAN, RESIKO BISNIS DAN PERTUMBUHAN AKTIVA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2005-2007 - Saragih, Joana L. (UNIKA Santo Thomas, 2010)
A decision on a capital structure (ratio between share and loan capitals) done by a financial manager is an important decision. This is due to its influence upon risks undergone and profits expected by shareholders. These analyses are used to solve the problem which is whether the size of the firm, the business risks, the growth of assets, the profitability and the ownership structure influence the capital strusture or not? The population in this research is the go public manufacturing sector in the Indonesia Stock Exchange for years 2005 until 2007. The sample is defined by cluster propotional random sampling to get a representative sample on each sector. There are 33 go public manufacturing companies selected as sample for this research. There are two variables in this research, the independent variable and dependent variable. The independent variable comprises firm size, business risk, growth of assets, and profitability; and for the dependent variable is the capital structure of go public manufacturing companies in the BEI. This research was analyzed using multiple regressions. This research found the empirical results that partially, SIZE influences positive significant and NPM influences negative significant to the capital structure of go public manufacturing companies in the Bursa Efek Indonesia. While the result of partial test for DOL and GROW showed that partially they didn’t influence significantly to the capital structure. The result for the simultaneous test showed that there is influence between SIZE, DOL, GROW, and NPM with the capital strusture of go public manufacturing companies in the Bursa Efek Indonesia. The influence is 0,197 or 19,7%. The other 80.3% influenced by another factors outside the research or the regression model.